Monks, Sovereigns, and Malign Spirits: Profiles of Tengu in Medieval Japan - Wakabayashi, Haruko (Religion compass, 2013)
The most significant development in tengu images of medieval Japan is their association with ma (skt. Māra)—an evil that is specific to Buddhism, defined as a force that defies Buddhism or disturbs Buddhist monks and hinders them from attaining enlightenment. They appear as malign spirits that seek to disturb the Buddhist Law and thereby bring chaos to the society, or as enemies of Buddhism that harass the monks and delude the people with their magic tricks. Monks who failed to attain enlightenment could also become a tengu, as they fell into the "realm of tengu" because of their conceit and worldly attachment. While most tengu are simply referred to as "tengu," we find several outstanding tengu from this period. This essay surveys various images of tengu prominent during the medieval period, particularly between the 12th and 15th centuries, in an effort to critically explore and understand the meanings attributed to these mythical creatures.